Implementasi Kebijakan Beasiswa Karawang Cerdas dalam Upaya Meningkatkan Kesejahteraan Pelajar di Kabupaten Karawang - Dandi Rahayu; Eka Yulyana; Rahman Rahman (Peneliti.net, 2021)
In the process of implementing the karawang cerdas policy, there are many parties who support it, but there are also those who are against the policy. To be able to examine the problem, the researcher uses Edward III's theory of policy implementation. This study uses a qualitative descriptive type, with data collection techniques carried out through interviews, observation and documentation. The results of this study indicate that the implementation of the karawang cerdas policy in communication has been successful with the understanding of every employee that makes it easier for the public to find out all forms of information about intelligent karawang but the government is considered not transparent, the resource authority over the implementation of smart karawang is contained in the regent's regulation number 66 of the year 2018 although there are still indications of non-compliance by both the organizers and scholarship recipients, the absence of intensive division and promotion in the disposition of employee performance and the bureaucratic structure of SOPs are carried out well by employees, but the inappropriate division of tasks causes errors in data collection.